Coating preparation process of recoverable high-barrier film

By combining graphene oxide with polyvinyl alcohol, crosslinked graphene polyvinyl alcohol composite material is prepared and applied to the surface of a five-layer coextruded film made of a single PE material, the problem of insufficient barrier performance of a single polyethylene film is solved and efficient barrier performance and recyclability are achieved.

CN119872050AActive Publication Date: 2025-04-25SUZHOU ZIJIN PLASTIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411937394.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-25
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The barrier properties of a single material are limited and cannot meet the actual use requirements of packaging materials. At the same time, traditional polyethylene films are not convenient for classification and recycling when recycling.

Method used

Through the independently developed urea-based POSS-based coupling agent, graphene oxide is combined with polyvinyl alcohol to prepare a cross-linked graphene polyvinyl alcohol composite material, and the coating solution is applied to the surface of a five-layer coextruded film made of a single PE material to form a coated recyclable high-barrier film.

Benefits of technology

It significantly reduces the oxygen permeability and water vapor permeability, improves the barrier performance of the film, and is easy to recycle and recycle due to the use of a single PE material, which is in line with the trend of environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119872050A_ABST
    Figure CN119872050A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating type high-barrier film research and development, and discloses a coating type recyclable high-barrier film preparation process which comprises the following steps: preparing a ureido POSS (Polyhedral Oligomeric Silsesquioxane)-based coupling agent; the preparation method comprises the following steps: carrying out surface modification treatment on graphene oxide by using a ureido POSS-based coupling agent to prepare ureido POSS-based graphene; the preparation method comprises the following steps: carrying out hydrogen-bond interaction on a ureido functional group contained on the surface of ureido POSS-based graphene and a hydroxyl functional group of polyvinyl alcohol, and compounding the ureido POSS-based graphene and polyvinyl alcohol to prepare the cross-linked graphene polyvinyl alcohol composite material. A cross-linked graphene polyvinyl alcohol composite material is dissolved to prepare a coating liquid, the surface of a five-layer co-extrusion film made of a single PE material is coated with the coating liquid, the coating type recoverable high-barrier film is prepared and obtained, the film coating has excellent barrier performance, the single PE material is adopted, recycling is convenient, and the coating type recoverable high-barrier film can be applied to the packaging field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of research and development of coated high-barrier films, and in particular to a coating preparation process for a recyclable high-barrier film. Background Art

[0002] With the increasing white pollution and the daily consumption of non-renewable resources such as oil, the preparation of new recyclable packaging materials to replace traditional packaging materials has become a hot topic in the packaging field. Polyethylene (PE) is a polymer material with excellent low temperature resistance, toughness, tensile strength and elongation. Polyethylene film is widely used in the packaging materials of food, medicine, electronic products, etc., and single-material polyethylene film does not need to be sorted when recycled, and can be 100% recycled, which has gradually become a trend in the development of the packaging industry. However, the barrier properties of single-material polyethylene film are limited and cannot meet the requirements of actual use of packaging materials.

[0003] Polyvinyl alcohol (PVA) is a biodegradable, recyclable and environmentally friendly material with high barrier properties. In the prior art, it has been reported that it is dissolved in water and coated on the surface of packaging film to improve barrier properties. In addition, graphene oxide (GO) has rich functional groups on its surface, which makes it very easy to achieve functional modification and improve its interfacial compatibility and interfacial force with the polymer matrix. Graphene oxide has a relatively high aspect ratio, which can provide a longer propagation path for penetrating molecules, and is an ideal filler for improving the barrier properties of polymers. Summary of the invention

[0004] The present invention combines graphene oxide and polyvinyl alcohol with excellent barrier properties through a self-developed urea-based POSS-based coupling agent to obtain a novel cross-linked graphene polyvinyl alcohol composite material, which is made into a coating liquid and smeared on the surface of a five-layer co-extruded film of a single PE material to prepare a thin film coating. The thin film coating has excellent barrier properties, and the single PE material is used for easy recycling and cyclic utilization, which is in line with the trend of environmental protection.

[0005] A process for preparing a coated recyclable high barrier film comprises the following steps:

[0006] Step 1: preparing a urea-based POSS-based coupling agent;

[0007] Step 2: The Si-OH functional group obtained by the hydrolysis reaction of the methoxy group of the urea-POSS-based coupling agent undergoes a dehydration condensation reaction with the -OH functional group of the graphene oxide, and the urea-POSS-based coupling agent is modified on the surface of the graphene oxide to prepare the urea-POSS-based graphene;

[0008] Step 3: Compounding the urea-based POSS-based graphene with the polyvinyl alcohol through hydrogen bonding between the urea-based functional groups on the surface of the urea-based POSS-based graphene and the hydroxyl functional groups of the polyvinyl alcohol to prepare a cross-linked graphene-polyvinyl alcohol composite material;

[0009] Step 4: dissolving the cross-linked graphene polyvinyl alcohol composite material to prepare a coating liquid, which is coated on the surface of a five-layer co-extruded film of a single PE material to prepare a coated recyclable high barrier film.

[0010] Preferably, the preparation method of the urea-based POSS-based coupling agent is:

[0011] Step S2-1: using trihydroxy heptaisobutyl POSS as a raw material and p-aminophenyltrimethoxysilane as a capping agent, synthesizing an phenylamino POSS-based monomer by a vertex-capping method;

[0012] Step S2-2: a urea-based POSS-based coupling agent is generated by a nucleophilic addition reaction between the isocyanate group of 3-isocyanate propyltrimethoxysilane and the amino functional group of the phenylamino POSS-based monomer.

[0013] Preferably, the formula and dosage of each film layer of the five-layer co-extruded film made of a single PE material are as follows:

[0014] First layer: the formula is 50-70wt% low-density polyethylene resin and 30-50wt% linear low-density polyethylene resin), the amount is 20-40 parts by weight;

[0015] The second layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight;

[0016] The third layer: the formula is 20-40wt% high-density polyethylene resin, 20-40wt% linear low-density polyethylene resin, 30-40wt% metallocene polyethylene resin and 1-10wt% ethylene-vinyl alcohol copolymer resin, the amount is 10-40 parts by weight;

[0017] The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight;

[0018] The fifth layer: the formula is 50-70wt% low-density polyethylene resin and 30-50wt% linear low-density polyethylene resin, and the amount is 20-40 parts by weight.

[0019] Preferably, the method for preparing the coated recyclable high barrier film is:

[0020] Step S4-1: pre-treating a five-layer co-extruded film made of a single PE material by washing it with a mixed solution consisting of 0.5 to 1.5 parts by volume of ethanol and 1 part by volume of deionized water and deionized water in sequence;

[0021] Step S4-2: dissolving 0.5 to 5 parts by weight of the cross-linked graphene polyvinyl alcohol composite material in a mixed solution consisting of 7 to 10 parts by volume of deionized water and 1 part by volume of N,N-dimethylformamide to prepare a cross-linked graphene polyvinyl alcohol composite material coating solution;

[0022] Step S4-2: evenly apply the cross-linked graphene polyvinyl alcohol composite material coating liquid on the surface of the five-layer co-extruded film of a single PE material, and dry it to obtain a coated recyclable high barrier film.

[0023] Preferably, the mass ratio of the urea-based POSS-based coupling agent, graphene oxide and polyvinyl alcohol in the cross-linked graphene polyvinyl alcohol composite material is 1:(1-5):(5-15).

[0024] Preferably, the graphene oxide has a sheet diameter of 1 to 3 μm and a thickness of 1 to 2 nm.

[0025] A coated recyclable high barrier film prepared according to the above process;

[0026] Preferably, the thickness of the five-layer co-extruded film of the single PE material is 80-120 μm, and the coating thickness of the cross-linked graphene polyvinyl alcohol composite material is 5-15 μm.

[0027] Preferably, the oxygen permeability of the coated recyclable high barrier film is (1.0-1.5) cm 3 / (m 2 ·24h·0.1MPa), water vapor transmission rate is (1.5~2.0)g / (m 2 ·24h).

[0028] Beneficial effects:

[0029] The present invention designs and synthesizes a urea-based POSS-based coupling agent, wherein the urea-based POSS-based coupling agent performs surface modification treatment on graphene oxide through a covalent bond action, and performs cross-linking and compounding with polyvinyl alcohol based on a hydrogen bond action, thereby preparing a cross-linked graphene polyvinyl alcohol composite material; finally, the cross-linked graphene polyvinyl alcohol composite material is made into a coating liquid and coated on the surface of a five-layer co-extruded film of a single PE material, thereby preparing a coated recyclable high-barrier film;

[0030] Through experiments, it is found that: compared with a five-layer co-extruded film made of a single PE material, the coated recyclable high-barrier film prepared by the present invention can significantly reduce oxygen permeability and water vapor permeability, showing excellent barrier properties;

[0031] It is also found that the coated recyclable high barrier film prepared by the present invention also has slightly improved mechanical properties and can be used in the packaging field. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 These are the performance test results of coated recyclable high barrier films. DETAILED DESCRIPTION

[0033] Experimental example:

[0034] Preparation of urea-based POSS-based coupling agent, the synthesis route is as follows:

[0035]

[0036] Step 1: using trihydroxy heptaisobutyl POSS as a raw material and p-aminophenyltrimethoxysilane as a capping agent, a phenylamino POSS-based monomer is synthesized by a vertex-capping method;

[0037] Step 2: a urea-based POSS-based coupling agent is generated by a nucleophilic addition reaction between the isocyanate group of 3-isocyanate propyltrimethoxysilane and the amino functional group of the phenylamino POSS-based monomer;

[0038] The specific experimental steps for preparing urea-based POSS-based coupling agent are:

[0039] 4.0 g of trihydroxy heptaisobutyl POSS and 40 mL of anhydrous tetrahydrofuran were added to a three-necked flask, and stirred at room temperature under nitrogen protection until all dissolved. After being placed in an ice-water bath and stirred for 30 min, 10 mL of anhydrous tetrahydrofuran solution containing 1.1 g of p-aminophenyltrimethoxysilane was added dropwise to the three-necked flask, and the mixture was stirred in an ice-water bath for 20 min and then stirred at room temperature for 7 days. Anhydrous methanol and acetonitrile were used for sedimentation, filtration, washing, and vacuum drying to obtain an phenylamino POSS-based monomer.

[0040] 3.0 g of aniline POSS-based monomer, 0.7 g of 3-isocyanate propyltrimethoxysilane and 40 mL of anhydrous tetrahydrofuran were added into a three-necked flask, and the temperature was raised to 70° C. under nitrogen protection and mechanical stirring for 5 h, and then cooled to room temperature, washed with anhydrous methanol, and vacuum dried to obtain a urea-based POSS-based coupling agent;

[0041] The nuclear magnetic resonance hydrogen spectrum of the urea-based POSS-based coupling agent is characterized as follows: 1 H NMR (DMSO-d 6, 400MHz) δ: 0.57-0.59 (d, 14H), 0.65-0.69 (t, 2H), 0.92-0.94 (d, 42H), 1.53-1.60 (m, 2H), 1.69- 1.79 (m, 7H), 3.14-3.19 (m, 2H), 3.57 (s, 9H), 6.53-6.56 (t, 1H), 7.40-7.61 (m, 4H), 8.87 (s, 1H).

[0042] Embodiment 1:

[0043] Preparation of urea-based POSS-based graphene: a Si-OH functional group obtained by hydrolysis of the methoxy group of the urea-based POSS-based coupling agent undergoes a dehydration condensation reaction with the -OH functional group of the graphene oxide, and the urea-based POSS-based coupling agent is modified on the surface of the graphene oxide to prepare the urea-based POSS-based graphene;

[0044] The specific experimental steps for preparing urea-based POSS-based graphene are as follows: under nitrogen protection and mechanical stirring, 2 g of urea-based POSS-based coupling agent, 5 g of graphene oxide, 20 mL of deionized water and 30 mL of anhydrous ethanol are added to a round-bottom flask, stirred and mixed at room temperature for 2 h, then 1 mL of ammonia water is added dropwise to the flask, the temperature is raised to 60 ° C, stirred and reacted for 4 h, washed with anhydrous ethanol, filtered, and vacuum dried to obtain urea-based POSS-based graphene;

[0045] Among them, graphene oxide was purchased from Nanjing Xianfeng Nanomaterials Co., Ltd., and its specifications are: sheet diameter 1-3 μm, thickness 1-2 nm.

[0046] Embodiment 2:

[0047] Preparation of a cross-linked graphene-polyvinyl alcohol composite material: the urea-based POSS-based graphene and the polyvinyl alcohol are compounded by hydrogen bonding between the urea-based functional groups on the surface of the urea-based POSS-based graphene and the hydroxyl functional groups of the polyvinyl alcohol to prepare a cross-linked graphene-polyvinyl alcohol composite material;

[0048] The specific experimental steps for preparing the cross-linked graphene polyvinyl alcohol composite material are as follows: 2 g of polyvinyl alcohol resin and 50 mL of deionized water are added to a three-necked flask, heated to 90 ° C and stirred to dissolve for 4 h, polyvinyl alcohol mother liquor is prepared, cooled to 60 ° C, 0.7 g of urea-based POSS-based graphene is added to the three-necked flask, maintained at 60 ° C and stirred for 5 h, mixed evenly, and a cross-linked graphene polyvinyl alcohol composite material is obtained;

[0049] Among them, polyvinyl alcohol resin was purchased from Dongguan Yingxiang Plastic Raw Materials Co., Ltd., and its model is 22-88.

[0050] Embodiment 3:

[0051] The preparation of coated recyclable high barrier film includes three preparation steps, as follows:

[0052] Step 1: Prepare a five-layer co-extruded film of a single PE material. The five-layer co-extruded film of a single PE material is designed to have a five-layer symmetrical film structure. A five-layer co-extruded film of a single PE material is prepared by a five-layer co-extrusion blow molding film forming process. The specific preparation process is as follows:

[0053] The raw materials of the first layer (formulated as 60wt% low-density polyethylene resin and 40wt% linear low-density polyethylene resin), the second layer (formulated as 100wt% maleic anhydride grafted polyethylene resin), the third layer (formulated as 30wt% high-density polyethylene resin, 30wt% linear low-density polyethylene resin, 35wt% metallocene polyethylene resin and 5wt% ethylene-vinyl alcohol copolymer resin), the fourth layer (formulated as 100wt% maleic anhydride grafted polyethylene resin), and the fifth layer (formulated as 60wt% low-density polyethylene resin and 40wt% linear low-density polyethylene resin) are respectively put into the hopper of the five-screw extruder of the five-layer co-extrusion film blowing unit according to the mass ratio of 30:5:30:5:30, after stirring and mixing, the molten resin is merged at the head of the die through the diverter, and is extruded and blown through the die head, the traction speed is 6m / min, and the blow-up ratio is controlled at 2.6, to obtain a five-layer co-extruded film of a single PE material with a thickness of 100μm;

[0054] A five-layer co-extruded film made of a single PE material was fixed on a wire frame, placed in an ethanol solution (the volume ratio of ethanol to deionized water was 1:1) for cleaning for 2 hours, then washed with deionized water, and dried at 45°C for later use;

[0055] The process parameters of the screw extruders of the first, second, fourth and fifth layers were set as follows: the temperatures of zones 1-3 were 130°C, 150°C and 180°C respectively, the flow channel temperature was 170°C, and the rotation speed was 30r / min;

[0056] The process parameters of the screw extruder of the third layer are set as follows: the temperatures of zones 1-3 are 140°C, 170°C, and 190°C, respectively, the flow channel temperature is 185°C, and the speed is 40r / min;

[0057] Step 2: preparing a cross-linked graphene polyvinyl alcohol composite material coating liquid, the specific preparation process of which is: mixing 3g of the cross-linked graphene polyvinyl alcohol composite material, 45mL of deionized water and 5mL of N,N-dimethylformamide, heating to 95°C and stirring until all dissolved, cooling to room temperature, and obtaining a cross-linked graphene polyvinyl alcohol composite material coating liquid;

[0058] Step 3: Fix the five-layer co-extruded film of a single PE material on the coating machine, use a 5μm metering rod to evenly apply the cross-linked graphene polyvinyl alcohol composite material coating liquid on the surface of the five-layer co-extruded film of a single PE material, put it in a 70°C oven and dry it for 3 hours to obtain a coated recyclable high barrier film;

[0059] Among them, low-density polyethylene resin (brand name LD 150DW) was purchased from Jiangsu Rantai Plastic Co., Ltd.; linear low-density polyethylene resin (brand name 2045G) was purchased from Yuyao Hongyang Plastic Co., Ltd.; metallocene polyethylene resin (brand name SP4020) was purchased from Dongguan Jinshixiang Plastic Raw Materials Co., Ltd.; high-density polyethylene resin (brand name FB5600) was purchased from Dongguan Longhuang Plastic Raw Materials Co., Ltd.; ethylene-vinyl alcohol copolymer resin (brand name ET3803RB) was purchased from Guangzhou Best New Material Technology Co., Ltd.; maleic anhydride grafted polyethylene resin (brand name 4288) was purchased from Dongguan Taotao Plastic Raw Materials Co., Ltd.

[0060] Performance Test:

[0061] 1. Barrier performance test:

[0062] (1) Use a Y110 oxygen permeability tester to test the oxygen barrier properties of the sample in accordance with GB / T 1038-2000 and record the oxygen permeability of the sample;

[0063] (2) Use TC-03 water vapor transmission meter to test the water barrier properties of the sample in accordance with GB / T 1037-2021 and record the water vapor transmission rate of the sample;

[0064] 2. Mechanical properties:

[0065] The mechanical properties of the samples were tested using an Instron 5565 universal tensile testing machine. The specific test steps are as follows: a 150 mm × 20 mm sample was fixed on the tensile testing machine, and a tensile test was performed at a tensile rate of 5 mm / min, and the longitudinal and transverse tensile strengths of the samples were recorded;

[0066] The above test results are shown in Table 1 below.

[0067] Table 1 Performance test results of coated recyclable high barrier film

[0068]

[0069]

[0070] The test data in Table 1 are plotted. Figure 1 , through comprehensive analysis of the above experimental results, we can draw the following conclusions:

[0071] (1) Compared with a five-layer co-extruded film made of a single PE material, the coated recyclable high-barrier film prepared by the present invention can significantly reduce oxygen permeability and water vapor permeability, showing excellent barrier properties;

[0072] (2) The coated recyclable high barrier film prepared by the present invention also has slightly improved mechanical properties.

Claims

1. A process for preparing a coated recyclable high barrier film, characterized in that: The following steps are involved: Step 1: prepare a urea-based POSS-based coupling agent, the chemical structure of which is: Step 2: The Si-OH functional group obtained by the hydrolysis reaction of the methoxy group of the urea-POSS-based coupling agent undergoes a dehydration condensation reaction with the -OH functional group of the graphene oxide, and the urea-POSS-based coupling agent is modified on the surface of the graphene oxide to prepare the urea-POSS-based graphene; Step 3: Compounding the urea-based POSS-based graphene with the polyvinyl alcohol through hydrogen bonding between the urea-based functional groups on the surface of the urea-based POSS-based graphene and the hydroxyl functional groups of the polyvinyl alcohol to prepare a cross-linked graphene-polyvinyl alcohol composite material; Step 4: dissolving the cross-linked graphene polyvinyl alcohol composite material to prepare a coating liquid, which is coated on the surface of a five-layer co-extruded film of a single PE material to prepare a coated recyclable high barrier film.

2. The process for preparing a coating-type recyclable high-barrier film according to claim 1, characterized in that: The preparation method of the urea-based POSS-based coupling agent is: Step S2-1: using trihydroxy heptaisobutyl POSS as a raw material and p-aminophenyltrimethoxysilane as a capping agent, synthesizing an phenylamino POSS-based monomer by a vertex-capping method; Step S2-2: a urea-based POSS-based coupling agent is generated by a nucleophilic addition reaction between the isocyanate group of 3-isocyanate propyltrimethoxysilane and the amino functional group of the phenylamino POSS-based monomer.

3. The process for preparing a coating-type recyclable high-barrier film according to claim 1, characterized in that: The formula and dosage of each film layer of the five-layer co-extruded film of single PE material are as follows: First layer: the formula is 50-70wt% low-density polyethylene resin and 30-50wt% linear low-density polyethylene resin), the amount is 20-40 parts by weight; The second layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight; The third layer: the formula is 20-40wt% high-density polyethylene resin, 20-40wt% linear low-density polyethylene resin, 30-40wt% metallocene polyethylene resin and 1-10wt% ethylene-vinyl alcohol copolymer resin, the amount is 10-40 parts by weight; The fourth layer: the formula is 100wt% maleic anhydride grafted polyethylene resin, the amount is 3 to 8 parts by weight; The fifth layer: the formula is 50-70wt% low-density polyethylene resin and 30-50wt% linear low-density polyethylene resin, and the amount is 20-40 parts by weight.

4. The process for preparing a coating-type recyclable high-barrier film according to claim 1, characterized in that: The preparation method of the coated recyclable high barrier film is as follows: Step S4-1: pre-treating a five-layer co-extruded film made of a single PE material by washing it with a mixed solution consisting of 0.5 to 1.5 parts by volume of ethanol and 1 part by volume of deionized water and deionized water in sequence; Step S4-2: dissolving 0.5 to 5 parts by weight of the cross-linked graphene polyvinyl alcohol composite material in a mixed solution consisting of 7 to 10 parts by volume of deionized water and 1 part by volume of N,N-dimethylformamide to prepare a cross-linked graphene polyvinyl alcohol composite material coating solution; Step S4-2: evenly apply the cross-linked graphene polyvinyl alcohol composite material coating liquid on the surface of the five-layer co-extruded film of a single PE material, and dry it to obtain a coated recyclable high barrier film.

5. The process for preparing a coating-type recyclable high-barrier film according to claim 1, characterized in that: The mass ratio of the urea-based POSS-based coupling agent, graphene oxide and polyvinyl alcohol in the cross-linked graphene polyvinyl alcohol composite material is 1:(1-5):(5-15).

6. The process for preparing a coating-type recyclable high-barrier film according to claim 5, characterized in that: The sheet diameter of the graphene oxide is 1 to 3 μm and the thickness is 1 to 2 nm.

7. A coated recyclable high barrier film prepared by the process according to any one of claims 1 to 6, characterized in that: The thickness of the five-layer co-extruded film made of a single PE material is 80 to 120 μm, and the coating thickness of the cross-linked graphene polyvinyl alcohol composite material is 5 to 15 μm.

8. The coated recyclable high barrier film according to claim 7, characterized in that: The oxygen permeability of the coated recyclable high barrier film is (1.0-1.5) cm 3 / (m 2 ·24h·0.1MPa), water vapor transmission rate is (1.5~2.0)g / (m 2 ·24h).

9. Use of a coated recyclable high barrier film prepared according to the process according to any one of claims 1 to 6 in the field of packaging.

Citation Information

Patent Citations

  • Flame-retardant polylactic acid material and preparation method thereof

    CN115160749A

  • Preparation method of high-barrier polyvinyl alcohol packaging film

    CN118420959A